Biomechanical analyses of the handstand: a systematic review - McDonald, M.; Baker, J. S.; Gu, Y.; Ugbolue, U. C. (Frontiers in Sports and Active Living, 2025)
Purpose: The aim of this systematic review was to investigate the biomechanical analysis of the handstand. Methods: Systematic searches were conducted using databases SPORTDiscus, ScienceDirect, and PubMed up to August 2025. The search included the following terms: "EMG or Electromyography and Handstand AND Gymnastics," "Kinetics AND Kinematics and Handstand AND Gymnastics," "Kinetics AND Handstand," and "Kinematics AND Handstand." Initially, 491 publications were identified. Of these, 21 studies were included in this systematic review, each of which conducted a biomechanical analysis of the handstand. Data from the 21 articles were extracted to conduct a biomechanical analysis of the handstand. Results: Of the included studies, 31% analyzed balance control strategies of the handstand, 57% performed a kinetic and kinematic analysis of the handstand, and 10% compared muscle activity during the handstand. Furthermore, 42% of the publications analyzed the center of pressure of the handstand, 36% analyzed joint angles, 21% reported on velocity, 21% examined joint torque contributions, 15% investigated angular velocity, 10% analyzed ground reaction forces (GRFs), 10% investigated electromyography (EMG) data, and 5% assessed vertical ground reaction forces (vGRFs). Conclusion: The findings of this study indicate that gymnasts minimize problems related to disturbed balance during the handstand using a "wrist strategy" to secure a fixed-body configuration. If the "wrist strategy" fails, then the wrists, shoulders, hips, and elbows are utilized, which can be interpreted as a mixed control strategy. Visual conditions and head positions also affect handstand balance. In particular, closing the eyes leads to decreased stability, and neck flexion impairs performance during the handstand. Gymnasts with greater strength possess better balance control. Other factors that also influence handstand performance are participation level and age of the performers.